Troska o więźniów w nauczaniu papieża Franciszka - Michał Borda (Wrocławski Przegląd Teologiczny)
The article gets itself into the preaching of the Pope Francis, thanks to which we are experiencing the Jubily of Mercy. While preparing the Holly Year, as well as during its duration, prisoners are taking a special position in it. The concern of those who experience the restriction of their freedom is characterized by, since the very beginning, the Pope Francis’s pontificate. The analysis of the Pope Francis’s preaching directed to those imprisoned in the prisons makes it possible to isolate the main topics: the rule of christcentrism, emphesizing the dignity of every human being and the call for social re-integration. It is worth having a close look in order to experience the Jubilee of Mercy in a more fructuous way.